Intellectual property protection in healthcare sector -- advantages of original research focusing on financial aspect and application process - Novák, Ivan (2015)
Intellectual property (IP), is mostly associated with being immaterial. The term "property right" refers to a right or a set of rights one can enforce by means of benefits or use over a resource. Those rights may be transferable and may be treated as property or resources themselves. As from a historical point of view, different IP components developed independently on each other, this paper examines patents, utility models, registered designs, trademarks, and copyright individually. In order to answer the first research question "What means of protection are best suited for medical breakthroughs?", it adds a Supplementary Medical Certificate to a list of possible IPP tools. Even though this mean of protection is not recognized worldwide, it extends the regular protection period of a patent, and thus is commonly used. There are limitations to medical related IP protection as well, e.g. compulsory licensing which occurs when a government allows someone to produce a patented medication without the consent of the patent owner. IPP is also used to secure access to innovative and expensive medications in third world countries by tier pricing or licensing. The second research question "Under what circumstances is applying for a medical related trademark cost beneficial?" is answered through a case study. Its main goal is to extend on the theoretical part, and apply for a trademark with the Intellectual Property Office in Czech Republic (IPO CZ). In addition, the entire application process is thoroughly described and can serve as guideline for future applicants, not only with the IPO CZ as the application process with any national IP office is rather similar. In combination with a successful application, this is one of the most important findings.